Making ultrafine and highly-dispersive multimetallic nanoparticles in three-dimensional graphene with supercritical fluid as excellent electrocatalyst for oxygen reduction reaction. Issue 47 (21st November 2016) - Zhou, Yazhou; Yen, Clive H.; Hu, Yun Hang; Wang, Chongmin; Cheng, Xiaonong; Wai, Chien M.; Yang, Juan; Lin, Yuehe
Abstract : A powerful method of supercritical fluid was demonstrated to controllably synthesize porous graphene-based electrocatalysts by depositing ultrafine multimetallic nanoparticles. Abstract : Three-dimensional (3D) graphene showed an advanced support for designing porous electrode materials due to its high specific surface area, large pore volume, and excellent electronic property. However, the electrochemical properties of reported porous electrode materials still need to be improved further. The current challenge is how to deposit desirable nanoparticles (NPs) with controllable structure, loading and composition in 3D graphene while maintaining the high dispersion. Herein, we demonstrate a modified supercritical fluid (SCF) technique to address this issue by controlling the SCF system. Using this superior method, a series of Pt-based/3D graphene materials with the ultrafine-sized, highly dispersive and controllable composition multimetallic NPs were successfully synthesized. Specifically, the resultant Pt40 Fe60 /3D graphene showed a significant enhancement in electrocatalytic performance for the oxygen reduction reaction (ORR), including a factor of 14.2 enhancement in mass activity (1.70 A mgPt −1 ), a factor of 11.9 enhancement in specific activity (1.55 mA cm −2 ), and higher durability compared with that of Pt/C catalyst. After careful comparison, the Pt40 Fe60 /3D graphene catalyst shows the higher ORR activity than most of the reported similar 3D graphene-based catalysts. The successful synthesis of such attractive materials by this method also paves the way to develop 3D graphene in widespread applications.